University Students’ Coping Strategies in Blended Learning after The Pandemic COVID 19 - Erina Rahmajati; Hurul Aini Fatimah; Ahmad Zawawi; Fatehun Ni'am (Proceeding International Conference on Religion, Science and Education, 2023)
After the COVID 19 pandemic, in some universities, learning methods returned to offline methods gradually. Starting with the use of blended learning methods. But this situation makes students need to adapt again. One of the factors that support the success of this adaptation is the pattern of coping strategies developed by students. This article aims to describe the patterns of the universities students' coping strategies during this blended learning. Therefore interviews were conducted with six students who took part in this mixed lecture. From the exploration results obtained an overview of the three patterns of coping strategies that were formed in these students. The first pattern is students who have negative perceptions of the learning process but fail to do coping because they fail to do Accepting responsibility; while the second are those who have succeeded in overcoming emotional-oriented stress by carrying out Accepting responsibility and Positive reappraisal as well as problem-oriented coping by carrying out Planful problem solving and; third are students who have positive perceptions but also face problems in the middle of the lecture process, they are able to do emotion-oriented stress coping by doing Accepting responsibility and Positive reappraisal.